A priori audiovisual y paisajes de la diferencia: archivos, cuerpos, giros - Ciancio, María Belén (2024)
The audiovisual a priori, as a device and condition of actual enunciation that goes beyond a specific field, intersects with geographical-gendered intersectionality as a "landscape of difference". What does the weaving of feminisms, gender studies, and philosophical variations imply when we need to thinking about a production linked to the "regional turn" and the "archive turn", among others? How do these concepts relate to those produced around geoaesthetics, a geography of affects, and Deleuzo-Guattarian concepts: (de)territorialization, landscape, cinema and minor literature or the Third World? How can we critically approach a genealogy of the concept of region and of all the productions to which we usually attribute a subordinate, necessarily "independent" audiovisual identity? Rather than an analysis of films, this essay proposes a work in progress to map "minor", "border", "regional", mutant audiovisual forms, documentaries, filmed and audiovisual essays, and other forms produced or located outside a centralized region. It lies between geo-aesthetic and gender boundaries (as a social technology, performative technology, in relation to feminist, gender-dissident and non-binary activism) and what are usually considered "cinematic genres", which go beyond the national framework. However, it is also conceived as a series of first points of reference to un-automate the regionalist cartographic gesture, by questioning the way in which its scales, sometimes dual, its concepts, percepts, archives, and memories are constructed, within the framework of the studies and fields that address this cartography.